Papua New Guinea rural household survey (2023): Synopsis of selected results - Schmidt, Emily; Yadav, Shweta (International Food Policy Research Institute, 2024)
From May to December 2023, IFPRI implemented the 2023 PNG Rural Household Survey which was designed to understand rural livelihoods and welfare across different areas of PNG (Schmidt et al., 2024). Given the rural nature of the survey sample, almost all surveyed households depend on their own-farm production (predominantly starchy roots and tubers) to meet daily caloric needs. On average, households reported utilizing about 1.6 hectares of land for agriculture cultivation at the time of the survey. The survey collected a detailed account of the quantity of food types consumed by the household in order to estimate the average caloric intake per adult equivalent. Comparing the estimated caloric intake reported by surveyed households, with a recommended calorie intake suggests that only 45 per cent of individuals in surveyed households meet the recommended daily caloric intake for a lightly active individual. The survey also collected anthropometry data for children under five years of age and found that 36 percent of surveyed children were stunted in their growth. The 2023 Rural Household Survey represents an important effort in collecting a wide breadth of information about rural livelihoods. However, greater investments of in-depth data collection and analysis should be undertaken to examine specific components of PNG household livelihood strategies.